Analisis Makna Fukushi Taihen, Totemo, Nakanaka dan Hijou ni dalam Bahasa Jepang - Umi kalsum; Arza Aibonotika; Nana Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACTBecause of there are many meaning of taihen, totemo, nakanaka and hijouni in Japanese make the foreign language students have difficulty to differ the situation to use those fukushi. That is the background that make writer research what kind of meaning those fukushi had and to know if that fukushi to replace each other.From the results of research that being conducted by writer concluded that taihen means a word that shows emphasize to some condition added with exaggrated and neighborly element. Totemo emphasize againt some condition based on reality. Nakanaka used to emphasizing againts judgement that outside speaker’s expectation. Hijou ni is emphasize the changes that happened on certain circumstance followed with something that can become a benchmark which tell something changes. Next, those fukushi can replace each other but must be followed with certain situation and condition.keyword : analysis the meaning behavior, advervia taihen, totemo, nakanaka and hijou ni.